Fingolimod: a review of its mode of action in the context of its efficacy and safety profile in relapsing forms of multiple sclerosis. (2nd January 2016) - Jeffery, Douglas R; Rammohan, Kottil W; Hawker, Kathleen; Fox, Edward
Abstract : Fingolimod is an orally administered, first-in-class therapy for the treatment of relapsing forms of multiple sclerosis. Data from pivotal clinical trials show that fingolimod has a robust, significant effect on annualized relapse rates and MRI outcomes. Fingolimod has a novel, well-characterized mechanism of action. It acts through a specific set of receptors, sphingosine 1-phosphate receptors, present on the surface of a wide range of human cells and tissues, including neural cells, neurons and lymphocytes. Here we review the current literature to describe the mechanism of action of fingolimod in the context of its well-established clinical efficacy and safety profile. Understanding of the mechanisms behind any non-therapeutic effects of fingolimod facilitates their prediction and management in the clinical setting.